Unlocking the power of collaborative learning in secondary schools. : A transnational comparative analysis between Italy and Malta. - Baschiera, Barbara; Borg, Jonathan (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2023)
This paper presents a transnational comparative study on the use of Collaborative Learning (CL) techniques in lower and upper secondary classes in Italy and in Malta as it analyses the factors which impede its use. The qualitative analysis of open-ended questionnaire data, supplied by participating educators (30 Italian precarious teachers and 50 Maltese Learning Support Educators) at the end of their respective training courses, highlights an appreciation of CL practices besides strong criticism of the factors which inhibit the application of a student-centred philosophy. Findings indicate that teachers in Malta seem to be conditioned by postcolonial socio-cultural aspects, such as a highly centralised education system, a competitive exam-oriented approach to learning and a traditional curriculum-driven attitude to teaching; issues which debilitate the application of CL. Moreover, teachers are seen as reluctant to implement active learning techniques since these are perceived as non-compatible with the inclusion of all students. In contrast, systemic-organisational deficiencies for the recruitment of precarious Italian teachers discourage the use of CL. While resistance from colleagues, students and parents further demotivates upper secondary school teachers, lower secondary school teachers view schools as the ideal places for the experimentation of these techniques. The thematic analysis of focus group data implies an urgency to revisit the understanding of ‘education’ in Malta, the need for Italian teachers to collaborate with education stakeholders and the necessity of continued professional development which can empower teachers to proactively embrace a ‘methodological transition’ towards CL.